Navigating the Waters of Conflict: Indonesia and Malaysia's Maritime Boundary Dispute in the Sulawesi Sea and Malacca Straits - Gunawan, Yordan; Ansar, Muhammad Arya; Dzakiyyah, Siti Asdilla (Universitas Negeri Gorontalo, 2025)
This paper examined the maritime border disputes between Indonesia and Malaysia in the Straits of Malacca and Sulawesi Sea. The research comprehensively examined the historical backdrop, current disputes, and recent accords reached following 18 years of discussions. The primary emphasis lies in contrasting the negotiation strategies employed by the two countries with alternative methods of resolving conflicts, such as litigation. The study applied normative legal research methodologies, utilizing a statutory, analytical, and prescriptive approach based on international law. It relied on secondary legal materials and related laws. The historical context highlighted the importance of the Strait of Malacca as a vital maritime passage and the difficulties arising from conflicting claims and territorial sea limits. The study subsequently explored the techniques for resolving conflicts, specifically focusing on the significance of international law, namely the United Nations Convention on the Law of the Sea (UNCLOS).